Digital Transformation in a South African retail organization - Nnzeru, Tshisevhe (University of the Witwatersrand, Johannesburg, 2023)
Digital Transformation is at the heart of the Fourth Industrial Revolution and much of the research claims that an organization’s success is increasingly dependent on their ability to exploit DT with the e-Commerce industry being significant globally. While South Africa’s digital transformation is materially behind developed nations, retailers are gearing up for growth by digitally transforming their operations, not only to compete but remain relevant. Therefore, this research seeks to understand the successful implementation of Digital Transformation in a South African retail context. The Technology, Organization and Environment Framework was selected as the theoretical framework to guide the research design and interpret findings. The research question for the study is What does successful DT implementation in a SA retail organization entail? To answer this research question, an interpretivist qualitative, case study research design was employed. Data from a retailer undergoing Digital Transformation was collected through ten semi-structured interviews using an Interview guide and analyzed using Content analysis method. Findings reveal that Digital Transformation is not about Technology, it is organizational transformation encompassing transformational leadership, strategy development and implementation aligned with overall business strategy, technology as an enabler for transformation, empowerment of the workforce with digital skills and a conducive digital culture characterized by learning, change, innovation and adaptability. Findings also indicate that the added complexities of legacy environments cannot be underestimated for traditional brick-and-mortar retailers. In essence, DT is about people embracing change – not technology. As limited research has been conducted and published regarding the South African retail DT context, these findings contribute to the limited existing knowledge base with empirical findings, specifically, contributing important knowledge on what specific aspects need to be considered and accounted for when conducting DT and proved TOE Framework to be useful for understanding large digital disruption. For practitioners this research contributes a holistic approach to implementing DT beyond technology which includes transformational leadership, Digital Transformation Strategy development and alignment with overall business strategy, empowering people with digital skills and a digitally enabled culture with digital technology as an enabler for Digital Transformation. Furthermore, to be successful with Digital Transformation, it becomes essential for organizations to manage the added complexities of legacy environments and lastly, for entrenched workforces to realize that Digital Transformation is a necessity for business survival and adapt.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Commerce to the Faculty of Commerce, Law and Management, School of Business Sciences, University of the Witwatersrand, Johannesburg, 2023
Keywords: Adaptability; Agility; Digital Transformation; e-Commerce; Digital technologies; Digital workplace skills; Fulfillment; Omni-channel; Online retail; Organization and Environment Model; UCTD; SDG-9: Industry, innovation and infrastructure